The effectiveness of Instagram Advertising for Digital Marketing Strategy: Systematic Literature Review - Rahayuningrat, Prahita Sri; Ardiani, Gusti Tia; Alisa, Juniar; Sugiarti, Rubiah; Taufik, Nuryanti (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
This systematic literature review study aims to understand the effectiveness of Instagram advertising for digital marketing. It used online data from Google Scholar and Proquest with the keywords "effectiveness" AND "Instagram Advertising," which only uses papers reviewed for research. This study used PRISMA to create a systematic review. A total of 195 journal reviews were processed and then cleaned through specific criteria so that only 19 related papers were taken. From the 19 papers processed, it can be concluded that Instagram advertising is very effective in helping digital marketing. This research is expected to increase understanding for both practitioners and researchers regarding Instagram advertising and the use of PRISMA itself.